Laparoscopic retrieval of misplaced copper T - Gupta, Nishi; Chandra, Sukriti (International Journal of Research in Medical Sciences, 2018)
Intrauterine contraceptive device is important part of family planning services in India. These can be inserted post menstrually, post abortal, post-delivery or in post puerperal period. Associated complications include bleeding, pain, infection, expulsion and most serious complication as perforation of uterine wall and migration to adjacent organs. We present a case of successful laparoscopic retrieval of a misplaced cuT. A 30-year-old female para 2 live 1 presented in SDMH outpatient department with right sided lower abdominal pain since one year. NCCT scan of pelvis showed IUCD in pelvic cavity anteriorly just above urinary bladder. Laparoscopic removal of cuT was done along with tubal recanalization.